Inspiration vs. perspiration in economic development of the Former Soviet Union and China (ca. 1920–2010)1. Issue 1 (January 2015) - van Leeuwen, Bas; Didenko, Dmitry; Földvári, Péter
Abstract Here, we discuss the role of both perspiration factors (physical and human capital) and inspiration factors (Total Factor Productivity) in the economic development of the Former Soviet Union area (FSU) and China, ca. 1920–2010. Using a newly created dataset, we find that during the Socialist central‐planning period, economic growth in both countries was largely driven by physical capital accumulation. This finding follows logically from the development policies in place at that time. During their transition periods, (i.e., starting from the late 1970s in China and the late 1980s in the FSU), China managed to keep technical inefficiency of production factors in check, largely by massively increasing its human capital, thereby lowering the physical‐to‐human capital ratio. In contrast, the FSU accomplished a similar outcome largely through reducing its stock of physical capital. As a result, although there was little difference in technical efficiency between these two economies, China's emphasis on human capital formation made it easier for this country to improve its general productivity and to increase per capita growth. This changed in the late 1990s and early 2000s, when the FSU began to recover economically, regaining its 1990 levels of output and productivity.